Analysis of directional neighbour discovery process in millimetre wave wireless personal area networks. Issue 2 (1st June 2013) - Kim, Meejoung; Kim, Yong Sang; Lee, Wooyong
Abstract : The millimetre wave (mmWave) band offers the potential for multi‐gigabit indoor wireless personal area networks (WPANs). However, it has problems such as a short wavelength. To compensate, utilisation of directional antennas at the physical layer is recommended. For communications using this band, neighbour discovery using directional antennas (D‐ND) is one of the crucial steps. In this study, the D‐ND process is analysed mathematically for mmWave WPANs based on the concept of an exclusive region, and the values that are derived from the effect of using directional antennas. Maximising the neighbour discovery probability for a given amount of time is considered as an objective function. Performance measures are derived in closed forms, such as the probability of discovering a device for one self‐advertising packet and the power‐efficient sojourn time of a device in one direction. Numerical results are obtained using parameters based on the IEEE 802.15.3c standard. The results show that the efficiency of the D‐ND depends not only on how often devices transmit a self‐advertising packet, but also on antenna properties such as beamwidth. The mathematical analysis provides a theoretical basis for the D‐ND process, and the obtained results illustrate the physical layer impact on neighbour discovery.